A Spatio-Temporal Assessment of the Greeneries Within Enugu Urban Using GIS and Remote Sensing - Nnam, V.; Odumosu, J.; Ehirim-Mgbada, A.; Taribio, C.; Ozonyia, T. (Journal of Spatial Information Sciences, 2024)
This study addresses the imperative of preserving green spaces in urban environments amidst escalating urbanization, impacting greenery and posing environmental and societal concerns. Leveraging remote sensing data, particularly the Normalized Difference Vegetation Index (NDVI) and Soil Adjusted Vegetation Index (SAVI), the research employs advanced Geographic Information System (GIS) methods to assess greenery within Enugu Urban. The NDVI and SAVI being crucial for monitoring vegetation health in diverse contexts, are applied to high-resolution Landsat images, facilitating a precise evaluation of greenery trends. The study reveals a continuous decline in greenery. While the NDVI analysis reveal reduction in greeneries area from 65% to 12% between 1999 and 2022, the SAVI analysis shows similarly trend reducing from 53% to 6% within same period. These alarming reduction rate and trend as obtained from both NDVI and SAVI analyses, highlights the urgent need for afforestation initiatives within Enugu Urban. The consistency in the results obtained from both the NDVI and SAVI indices indicate their suitability for monitoring vegetation health and presence in urban and mixed land-use environments.